Co-creating authentic travel experiences: exploring the travel experiences of young Indian tourists - -, Mohd. Abad; Ahmad Shah, Firdous; -, Abdul Qadir (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
The demography of the metropolitan region of Delhi NCT and its demand for travel experiences is dynamic and ever-evolving. The present study explores the narratives that are developed through interaction between young Indian travelers and the local service providers during the process of co-creating authentic travel experiences. The authors preferred a qualitative research design with the sub-set of a narrative approach to pursue this study. Data has been collected from 18 study participants from the Delhi NCT region, and thematic analysis has been applied to identify different taxonomies under three primary themes. The study collates the evidence wherein the motivations and satisfaction from travel experiences have been revealed by assessing co-creation between travelers and service providers.